A Research on the Attitude of Occupational Safety Specialist Candidates Towards Their Profession - Cerev, Gökçe; Yenihan, Bora (Bingol University, 2021)
The purpose of this study is to measure the attitudes of occupational safety specialist candidates towards their profession. Individuals’ attitudes towards their profession are essential in terms of their career, productivity, and future. In general, individuals who have positive attitudes towards their profession have a more successful professional life. Occupational safety experts’ attitudes towards their profession are important both for their individual development and for the successful implementation of occupational health and safety principles. There is no study in the literature on the attitudes of occupational safety specialist candidates towards their profession. The study was carried out to fill the gap in the literature. In the study, the level of attitudes of occupational safety specialist candidates towards their profession was investigated by the survey method, one of the quantitative research methods. The participants’ occupational attitudes in general and in the sub-dimensions of love, value, and harmony were evaluated. As a result of the study, the data were stored into the SPSS 25.0 program. The data analysis revealed that occupational safety specialist candidates had high positive attitudes towards their profession, and that demographic characteristics such as gender and marital status did not affect attitudes, while the age variable was effective. Participants’ willingness to work and their evaluation of their profession as their ideal profession positively affected their professional attitudes. As a result of the study, it was concluded that it is important to ensure the sustainability of the high professional attitudes of the occupational safety specialist candidates. Improving the working conditions of the occupational safety specialist profession, increasing personal rights and protecting the education level are necessary elements for maintaining positive professional attitudes.

Bu çalışmanın amacı iş güvenliği uzmanı adaylarının mesleklerine yönelik tutumlarını ölçmektir. Bireylerin mesleklerine karşı sahip olduğu tutumlar kariyerleri, verimlilikleri ve gelecekleri açısından önemlidir. Genel olarak mesleklerine karşı olumlu tutumlara sahip bireyler daha başarılı bir meslek hayatına sahiptirler. İş güvenliği uzmanlarının da mesleklerine karşı tutumları hem bireysel gelişimleri hem de iş sağlığı ve güvenliği esaslarının başarılı bir şekilde uygulanması açısından önemlidir. Literatürde iş güvenliği uzmanı adaylarının mesleklerine ilişkin tutumlarına yönelik çalışma bulunmamaktadır. Çalışma literatürde bulunan eksikliğin giderilmesi için yapılmıştır. Çalışmada iş güvenliği uzmanı adaylarının mesleklerine karşı sahip olduğu tutumların düzeyi nicel araştırma metotlarından anket yöntemi ile araştırılmıştır. İş güvenliği uzmanı adaylarının mesleki tutumları genel boyutla birlikte sevgi, değer ve uyum alt boyutlarında incelenmiştir. Çalışmada veriler SPSS 25.0 programında değerlendirilmiştir. Verilerin değerlendirilmesi sonucunda iş güvenliği uzmanı adaylarının mesleklerine karşı yüksek olumlulukta tutumlara sahip olduğu, demografik özelliklerden cinsiyet ve medeni durumun mesleki tutumlara etkisi olmazken, yaş değişkenin mesleki tutumlara etkide bulunduğu tespit edilmiştir. Katılımcıların çalışma istekleri ve mesleklerinin ideal meslek olarak değerlendirmeleri ise mesleki tutumlarına olumlu yönde etkide bulunmaktadır. Çalışma sonucunda iş güvenliği uzmanı adaylarının yüksek mesleki tutumlarının sürdürülebilirliğinin sağlanmasının önemli olduğu sonucu elde edilmiştir. İş güvenliği uzmanı mesleğinin çalışma şartlarının iyileştirilmesi, özlük haklarının artırılması ve eğitim seviyesinin korunması olumlu mesleki tutumların sürdürülebilmesi için gerekli unsurlardır.
İş Güvenliği Uzmanı Adaylarının Mesleklerine İlişkin Tutumları Üzerine Bir Araştırma
Keywords: Economics; Ekonomi